Aplikasi Pengenalan Tempat Dan Bangunan Bersejarah Bangka Belitung Berbasis Mobile - Redi, Redi; Fujiyanti, Linda; Setya Pratama, Muhammad (Jurnal Inovasi Teknologi Terapan, 2024)
The historical introduction application is an area that has information about historical heritage. However, not many people know about the history of the Bangka Belitung Islands province. In the current era, mobile applications are growing very rapidly, so it would be very good to create a media in the form of an information application for identifying historical places and buildings in the Bangka Belitung Islands province. The aim of this research is to introduce the history of cultural heritage in the Bangka Belitung Islands province by creating an application that can display images, videos, materials and descriptions of the application. Researchers hope that it will be easier for users to find out and study the application for recognizing historical places and buildings in the Bangka Belitung Islands province.